A new design for an artificial cell: polymer microcapsules with addressable inner compartments that can harbor biomolecules, colloids or microbial species. Issue 10 (17th August 2017) - Lu, Annie Xi; Oh, Hyuntaek; Terrell, Jessica L.; Bentley, William E.; Raghavan, Srinivasa R.
Abstract : Multicompartment capsules with control over the contents of each inner compartment are prepared by a simple, oil-free technique. Abstract : Eukaryotic cells have an architecture consisting of multiple inner compartments (organelles) such as the nucleus, mitochondria, and lysosomes. Each organelle is surrounded by a distinct membrane and has unique internal contents; consequently, each organelle has a distinct function within the cell. In this study, we create biopolymer microcapsules having a compartmentalized architecture as in eukaryotic cells. To make these capsules, we present a biocompatible method that solely uses aqueous media ( i.e., avoids the use of oil phases), requires no sacrificial templates, and employs a minimal number of steps. Our approach exploits the electrostatic complexation of oppositely charged polymers dissolved in aqueous media. Specifically, droplets of an anionic biopolymer are generated using a simple microcapillary device, with the droplets being sheared off the capillary tip by pulses of gas (air or nitrogen). The liquid droplets are then introduced into a reservoir whereupon they encounter multivalent cations as well as a cationic biopolymer; thereby, a solid shell is formed around each droplet by electrostatic interactions between the polymers while the core is ionically cross-linked into a gel. In the next step, a discrete number of these capsules are encapsulated within a larger outer capsule by repeating the same process with a wider capillary. Our approach allows us to control the overall diameter of these multicompartment capsules (MCCs) (∼300–500 μm), the diameters of the inner compartments (∼100–300 μm), and the number of inner compartments in an MCC (1 to >5). More importantly, we can encapsulate different payloads in each of the inner compartments, including colloidal particles, enzymes, and microbial cells, in all cases preserving their native functions. A hallmark of biological cells is the existence of cascade processes, where products created in one organelle are transported and used in another. As an initial demonstration of the capabilities afforded by our MCCs, we study a simple cascade process involving two strains of bacteria ( E. coli ), which communicate through small molecules known as autoinducers. In one compartment of the MCC, we cultivate E. coli that produces autoinducer 2 (AI-2) in the presence of growth media. The AI-2 then diffuses into an adjacent compartment within the MCC wherein a reporter strain of E. coli is cultivated. The reporter E. coli imbibes the AI-2 and in turn, produces a fluorescence response. Thus, the action (AI-2 production) and response (fluorescence signal) are localized within different compartments in the same MCC. We believe this study is an important advance in the path towards an artificial cell.